2016
DOI: 10.1055/s-0042-101409
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric laser endomicroscopy can target neoplasia not detected by conventional endoscopic measures in long segment Barrett’s esophagus

Abstract: Methods and study aims: The incidence of esophageal cancer is rising despite increased surveillance efforts. Volumetric laser endomicroscopy (VLE) is a new endoscopic imaging tool that can allow for targeted biopsy of neoplasia in Barrett’s esophagus. We report a series of 6 patients with long-segment Barrett’s esophagus ( > 3 cm), who underwent a session of endoscopy with volumetric laser endomicroscopy, after a separate prior session of standard high-definition endoscopy with narrow band imaging (NBI) and ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 10 publications
(19 reference statements)
0
26
0
Order By: Relevance
“…The NvisionVLETM system was used in all studies [23][24][25][26][27][28][29]. Volumetric laser endomicroscopy is a second-generation optical coherence tomography.…”
Section: Equipment and Techniquesmentioning
confidence: 99%
See 3 more Smart Citations
“…The NvisionVLETM system was used in all studies [23][24][25][26][27][28][29]. Volumetric laser endomicroscopy is a second-generation optical coherence tomography.…”
Section: Equipment and Techniquesmentioning
confidence: 99%
“…Long segment imaging can be obtained with an axial resolution of 7 µm, a transverse resolution of about 30 µm, and can reach an imaging depth of up to 2 to 3 mm. A total of 1200 images can be obtained in 96 secs [23][24][25][26].…”
Section: Equipment and Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…8,9 In vivo case reports suggested that VLE could detect additional neoplasia, however, clinical trials in larger sample size are necessary to confirm these findings. 10 We envision that development of quantitative methods that enable red-flagging of areas suspicious for neoplasia, is important to aid endoscopists in real-time interpretation of VLE scans. In this study we examine such a quantitative method focusing on computer-aided detection.…”
Section: Introductionmentioning
confidence: 99%